Addressing astringency of grape seed extract by covalent conjugation with lupin protein - Cristhian Rafael Lopes Francisco; Siavash Soltanahmadi; Tatiana Porto Santos; Rosiane Lopes Cunha; Anwesha Sarkar (Current Research in Food Science)
Astringency of phenolic-rich foods is a key tactile perception responsible for acceptability/rejection of plant extracts as ingredients in formulations. Covalent conjugation of phenolic extracts with plant proteins might be a promising strategy to control astringency, but suffers from a lack of mechanistic understanding from the lubrication point of view. To shed light on this, this ex vivo study evaluated the effect of conjugation of a phenolic grape seed extract (GSE) with legume protein (lupin, LP) on tribological and surface adsorption performance of GSE in the absence and presence of human saliva (ex vivo). Tribological results confirmed GSE had an inferior lubrication capacity as compared to LP. The lubrication performance of LP-GSE dispersions was comparable to their corresponding LP dispersion (p > 0.05) when covalently conjugated with LP (LP-GSE) with increasing LP:GSE ratio up to 1:0.04 w/w and at a specific degree of conjugation (DC: 2%). Tribological and surface adsorption measurements confirmed the tendency of GSE to interact with human saliva (ex vivo, n = 17 subjects), impairing the lubricity of salivary films. The covalent bonding of LP to GSE hindered GSE's interaction with human saliva, implying the potential influence of covalent conjugation on attenuating astringency. LP appeared to compete with human saliva for surface adsorption and governed the lubrication behaviour in LP-GSE dispersions. Findings from this study provide valuable knowledge to guide the rational design of sustainable, functional foods using conjugation of phenolics with plant proteins to incorporate larger proportions of health-promoting phenolics while controlling astringency, which needs validation by sensory trials.